Tecnologia educacional para promoção da saúde mental de universitários ingressantes - Oliveira, Angellica Fernandes de (2024)
Objective: to develop an educational technology to promote the mental health of incoming university students. Method: This is a methodological study. The educational technology was built and validated in content, appearance and semantics. For its construction, two scoping reviews were carried out, entitled: Emotional intelligence in the university context and Interventions for promoting the mental health of university students. Based on the results of the reviews, the Theory of Transitions by Afaf Meleis and the Theory of Emotional Competencies of Emotional Intelligence by Daniel Goleman were considered for the construction of the booklet, and the booklet format consisted of six workshops to be self-carried out in six consecutive weeks. The content and appearance validation was carried out by experts using specific instruments. The Content Validity Index (IVC) was used for content validation, and the Appearance Validity Index (IVA) for appearance validation. The semantic validation was carried out by ten incoming university students (target audience) from a Federal University in Mato Grosso, using a specific instrument. Semantic validation was conducted by calculating the Semantic Validity Index (IVS), reliability by the intraclass correlation coefficient (ICC) and internal consistency (McDonald's Omega). Results: the results and discussion were prepared in the form of manuscripts. The booklet was considered valid in its content (Total-IVC=0.87). Two rounds were necessary for face validation, with the first round presenting Total-IVC=0.72 and the final round presenting Total-IVC=0.96. It was considered semantically valid with TotalIVC=0.80, with satisfactory reliability (ICC>0.50) and internal consistency (>0.70) indices. The final product of the Technology contains 36 colored pages arranged between cover, cataloging card, presentation, summary, workshops and references. Conclusion: The proposed educational technology presented evidence of content, appearance and semantic validity after evaluation by experts and target audience, with strong indications of importance and relevance for use among incoming university students with a view to promoting mental health.